Сравнительный анализ моделей конвективной теплоотдачи - Байда, Евгений Иванович (НТУ "ХПИ", 2011)
В статье рассмотрены различные модели конвективной отдачи тепла нагреваемым объектом. Проведен сравнительный анализ полученных результатов и даны количественные результаты расчета

In the article, different models of convection heat emission by a heated object are considered. A comparative analysis of results obtained is conducted, quantitative results of calculations given
Comparative analysis of convection heat emission models
Keywords: степень нагрева; нагреваемый объект; теплоизоляция; коэффициент теплоотдачи; heat emission; mathematical model; free convection; heat emission coefficient; convictive heat exchange